SYNTACTIC BEHAVIOUR OF NOUN IN MUNA LANGUAGE - Aderlaepe, Aderlaepe (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 19 (2012): March 2012, 2011)
This research is concerned with noun in Muna language with the main focus on  syntactic aspects particularly its syntactic behaviour.  The problem of the research is stated in the form of questions, as follows: (1) What are the kinds of language units function as modifiers of noun in Muna language? and  (2)  What syntactic functions can be filled by noun in Muna language?  The objective of this research is determined based on the problem.  Thereby, the objectives are:  (1) To describe and explain the language units function as modifiers of noun in Muna language and (2) To describe and explain the syntactic functions which can be filled by noun in Muna language.  The research is designed qualitatively, where the analysis is based on the language natural usage of Muna language by its speech community.  Data were gathered by using several techniques, namely: (1) observation, (2) interview, (3) note taking, (4) ellicitation, and (5) introspection.  The obtained data were analyzed by employing certain techniques,  they are:  (1) permutation, (2) substitution, and (3) expansion.  The results of the research are: noun in Muna language is not only modified by adjective, but also some other language units.  Noun in Muna language is modified by: (1) adjective;  (2) adverb: negative adverb soano ‘not’ and limitative adverb kaawu ‘only’;  (3) demonstratives aini ‘this’, aitu ‘that’,  atatu ‘that’, amaitu ‘that’, awaghaitu ‘that’, and anagha ‘that’;  (5) possesive;  and (6) quantitative: definite and indefinite quantitatives.  Definite quantitative as noun modifier in Muna language appears in the form of cardinal number, whereas the indefinite  o n e consists of two sub parts: variety quantitative sabhara ‘various’ and totality quantitative bhari-bharie ‘all’.  The other results of the research are:  noun in Muna language syntacticly can fill the functions of (1) subject of sentence, (2) predicate, (3) object which consists of  direct and indirect objects, and (4) complement of sentence that consists of  subjective and objective complements.  This phenomenon proves the difference of syntactic behavior of noun in Muna and English languages where noun in English language can not fill in predicate.
Keywords: language, syntactic behavior, noun, demonstrative, quantitative, and syntactic function